Towards an Interactive Experiment Framework: DynamiQ - Beuran, Razvan; Inoue, Tomoya; Yasuda, Shingo; Takano, Yuuki; Miyachi, Toshiyuki; Shinoda, Yoichi (EAI Endorsed Transactions on Cloud Systems, 2015)
Interactive network experiments are useful for finding solutions to network problems, for teaching and for training purposes. In this demonstration we shall present an interactive experiment framework that allows users to directly control the experiment scenario by using a touch panel interface. This framework uses the network emulation module named dynamiQ for the dynamic emulation of networks. The demonstration uses a scenario with up to 55 emulated nodes, out of which 30 nodes form an emulated vehicular network and 5 are static buildings. The other nodes represent wireless towers and unmanned aerial vehicles that can be freely placed in the virtual experiment area. Participants are tasked with creating a multi-hop mesh network for sending video traffic between two predefined remote lo- cations. A similar demonstration has already been shown at Interop Tokyo 2014, where it received a special jury award.